Simulation Study of Pin-Type Heatsinks on Convection Heat Transfer Characteristics in Electronic Devices - Chaniago, Noverto Zhorif; Alfian, Devia Gahana Cindi; Syaukani, Muhammad; Pujiyulianto, Eko; Nurullah, Fajar Perdana; Silitonga, Dicky Januarizky (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
Electronic components are components that require an optimal design in order to provide good heat release performance. The heat sink component is a relevant solution to help cool an electronic component by flowing heat energy into the environment either naturally or forcibly with the help of a fan. The purpose of this study is to determine the effect of material type on heat sink temperature distribution, determine the phenomenon of velocity boundary layer and thermal boundary layer that occurs in each heat sink variation, determine the effect of design shape and pin arrangement on pressure drop, determine the best design according to the final results of the study. This research uses 6 variations of design shape, 2 variations of arrangement (inline and staggered), and 3 types of materials (Aluminum, Copper, and Iron). The method used in this research is a simulation method with three stages of process, namely, pre processing, processing, and post processing. The results showed that copper material is the best in conducting heat with a temperature drop of 98.5% from the base temperature. The inline arrangement obtained a lower pressure drop than the staggered arrangement and the best design was obtained by fillet square perforation with an inline arrangement.